2022
DOI: 10.1097/fch.0000000000000346
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Exploration of Various Stigmas Impacting HIV Pre-Exposure Prophylaxis (PrEP) Uptake Among African American Young Adults

Abstract: Pre-exposure prophylaxis (PrEP) has promise for reducing racial/ethnic HIV disparities; yet, acceptance among African Americans remains low. PrEP-related stigmas may impact uptake, but this is understudied. This study examines mechanisms by which stigma impacts PrEP acceptance among various priority African American populations. Focus group data from 63 African American young adults (aged 18-29 years) in Louisville, Kentucky, explore how various stigmas impact attitudes toward PrEP. Data were analyzed using gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…22 Qualitative research has revealed that stigma around HIV, stigma related to PrEP and sexual behavior, and homophobia/transphobia each contribute to less PrEP utilization. 24 We observed that anxiety disorders were associated with a 72% greater odds of receiving PrEP and this is similar to the 67% increased likelihood of starting PrEP among those with an anxiety disorder in a nationally distributed medical record data base. 13 Although others have found no association between anxiety and willingness to start PrEP, 25 we have now shown a positive association between anxiety disorder and PrEP receipt in a national cohort and a multi-state health care system.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…22 Qualitative research has revealed that stigma around HIV, stigma related to PrEP and sexual behavior, and homophobia/transphobia each contribute to less PrEP utilization. 24 We observed that anxiety disorders were associated with a 72% greater odds of receiving PrEP and this is similar to the 67% increased likelihood of starting PrEP among those with an anxiety disorder in a nationally distributed medical record data base. 13 Although others have found no association between anxiety and willingness to start PrEP, 25 we have now shown a positive association between anxiety disorder and PrEP receipt in a national cohort and a multi-state health care system.…”
Section: Discussionsupporting
confidence: 67%
“… 22 Qualitative research has revealed that stigma around HIV, stigma related to PrEP and sexual behavior, and homophobia/transphobia each contribute to less PrEP utilization. 24 …”
Section: Discussionmentioning
confidence: 99%
“…According to CDC reports, there are several overarching challenges in HIV prevention, including issues related to awareness, treatment, equitable access to information, limited resources, stigma, complacency, and poverty (10). Studies on the challenges of PrEP awareness, initiation, and adherence highlight multiple factors, including stigma, medical mistrust, substance misuse, inequitable access and promotion, and high costs (11)(12)(13)(14)(15)(16)(17). Research examining what hinders an individual's movement along the PrEP Care Continuum has identified inadequate knowledge regarding how PrEP works, failure to translate PrEP's potential benefit to persons at higher risk of contracting HIV, and inaccurate information about PrEP limiting its initiation among populations experiencing disproportionate risk (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Some individuals may avoid seeking or staying on PrEP as a consequence of anticipated or experienced stigmatization [14]. Furthermore, stigma overlaps with HIVrelated stigma, in a way that fear of HIV may decrease PrEP uptake as it prevents individuals from openly talking about HIV [24]; similarly, it overlaps with homophobia, which is important because individuals might decline PrEP or stop using it because they may not want to be associated with a particular sexual orientation [24].…”
Section: Introductionmentioning
confidence: 99%